2017
DOI: 10.18632/oncotarget.15326
|View full text |Cite
|
Sign up to set email alerts
|

The TLR7 agonist imiquimod induces anti-cancer effects via autophagic cell death and enhances anti-tumoral and systemic immunity during radiotherapy for melanoma

Abstract: Toll-like receptor (TLR) ligands are strongly considered immune-adjuvants for cancer immunotherapy and have been shown to exert direct anti-cancer effects. This study was performed to evaluate the synergistic anti-cancer and anti-metastatic effects of the TLR7 agonist imiquimod (IMQ) during radiotherapy for melanoma. The pretreatment of B16F10 or B16F1 cells with IMQ combined with γ-ionizing radiation (IR) led to enhanced cell death via autophagy, as demonstrated by increased expression levels of autophagy-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 67 publications
6
71
0
Order By: Relevance
“…Among these studies, we found of particular interest the work of: (1) Molgora and colleagues (Humanitas Clinical and Research Center, Rozzano, Italy), who demonstrated that interleukin-1 receptor 8 (IL1R8, also known as TIR8 or SIGIRR), which is known to impair the signal transduction cascades elicited by several TLRs as well as by various interleukin receptors, 116,117 negatively regulates the activity of NK cells as an immunosuppressive checkpoint; 118 (2) Lou and co-authors (Institute for Molecular Bioscience. The University of Queensland, Brisbane, Australia), who showed that SLP adaptor and CSK interacting membrane protein (SCIMP), a transmembrane adaptor protein, facilitates TLR4 signaling upon direct binding to its TIR domain;- 119 , who demonstrated that the combination of a TLR3 agonist (ARNAX), 129,130 a PD-L1-specific immune checkpoint blocker and a TAA-derived vaccine may be used to overcome resistance to PD-1-targeting therapies, at least in mice; 131 (9) Caronni and colleagues (International Centre for Genetic Engineering and Biotechnology, Trieste, Italy), who found that lactic acid blocks the ability of DCs to produce type I IFN in response to TLR3 and STING agonists 132 in a mouse model of lung cancer; 133 confirming previous reports on the major influence of local metabolism on the immune functions of the tumor microenvironment; [134][135][136][137] (10) Dooduijn and collaborators (Leiden University Medical Center Leiden, The Netherlands), who showed that TLR7/TLR8 agonism, compared to TLR3 and TLR9 agonism, drives an NK cell-dependent immune response that can eradicate tumors that have escaped immunosurveillance following MHC Class I downregulation, 138 which is in line with data from other groups demonstrating the ability of TLR7 ligands to trigger NK celldependent tumor control; 75,[139][140][141][142] (11) Klein and co-authors (University Hospital Essen, Essen, Germany), who showed that mice lacking TLR3, TLR7 and TLR9 are able to reject syngeneic wild-type malignant cells upon the activation of a tumor-targeting immune response involving both CD4 + and CD8 + T lymphocytes, suggesting that endosomal TLRs may operate as part of immunological checkpoints, at least in some settings; 143 (12) Rashedi et al (University of Toronto, Toronto, Canada), who demonstrated that mesenchymal stromal cells recruit T REG cells- 144,145 upon TLR3 or TLR4 activation, as a consequence of Notch signaling modulation…”
Section: Preclinical and Translational Advancessupporting
confidence: 66%
“…Among these studies, we found of particular interest the work of: (1) Molgora and colleagues (Humanitas Clinical and Research Center, Rozzano, Italy), who demonstrated that interleukin-1 receptor 8 (IL1R8, also known as TIR8 or SIGIRR), which is known to impair the signal transduction cascades elicited by several TLRs as well as by various interleukin receptors, 116,117 negatively regulates the activity of NK cells as an immunosuppressive checkpoint; 118 (2) Lou and co-authors (Institute for Molecular Bioscience. The University of Queensland, Brisbane, Australia), who showed that SLP adaptor and CSK interacting membrane protein (SCIMP), a transmembrane adaptor protein, facilitates TLR4 signaling upon direct binding to its TIR domain;- 119 , who demonstrated that the combination of a TLR3 agonist (ARNAX), 129,130 a PD-L1-specific immune checkpoint blocker and a TAA-derived vaccine may be used to overcome resistance to PD-1-targeting therapies, at least in mice; 131 (9) Caronni and colleagues (International Centre for Genetic Engineering and Biotechnology, Trieste, Italy), who found that lactic acid blocks the ability of DCs to produce type I IFN in response to TLR3 and STING agonists 132 in a mouse model of lung cancer; 133 confirming previous reports on the major influence of local metabolism on the immune functions of the tumor microenvironment; [134][135][136][137] (10) Dooduijn and collaborators (Leiden University Medical Center Leiden, The Netherlands), who showed that TLR7/TLR8 agonism, compared to TLR3 and TLR9 agonism, drives an NK cell-dependent immune response that can eradicate tumors that have escaped immunosurveillance following MHC Class I downregulation, 138 which is in line with data from other groups demonstrating the ability of TLR7 ligands to trigger NK celldependent tumor control; 75,[139][140][141][142] (11) Klein and co-authors (University Hospital Essen, Essen, Germany), who showed that mice lacking TLR3, TLR7 and TLR9 are able to reject syngeneic wild-type malignant cells upon the activation of a tumor-targeting immune response involving both CD4 + and CD8 + T lymphocytes, suggesting that endosomal TLRs may operate as part of immunological checkpoints, at least in some settings; 143 (12) Rashedi et al (University of Toronto, Toronto, Canada), who demonstrated that mesenchymal stromal cells recruit T REG cells- 144,145 upon TLR3 or TLR4 activation, as a consequence of Notch signaling modulation…”
Section: Preclinical and Translational Advancessupporting
confidence: 66%
“…Upon screening for possible TLR ligands, we selected the TLR7 agonist (TLR7A) imiquimod as it has been used in the clinics for the treatment of nonmelanoma skin cancer but also melanoma . Furthermore, TLR7A has pleiotropic effects on T and NK cells and induces autophagic cell death in melanoma cells . Moreover, a recent study showed that a novel TLR7A reversed NK cell anergy and induced antitumor CD8 + T cell responses .…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30]36 Furthermore, TLR7A has pleiotropic effects on T and NK cells and induces autophagic cell death in melanoma cells. 37,38 Moreover, a recent study showed that a novel TLR7A reversed NK cell anergy and induced antitumor CD8 + T cell responses. 26,27 Therefore, we assessed if treatment with a TLR7A as an immune modulator would be efficient in prolonging sensitivity to BRAFi.…”
Section: Tumor-infiltrating T and Nk Cells Display An Activated Phenomentioning
confidence: 99%
“…The therapeutic effect of a TLR7 agonist (including IQM) or TLR7/8 dual agonist on melanoma growth in vivo has been previously reported (2,4,7,33). These reports revealed the immunostimulatory effect of these agonists through effector cells, such as CD8 + T cells, plasmacytoid DCs or M1 macrophages, and decrease the Tregs and MDSC in the tumor lesion, leading to the inhibition of B16F10 melanoma growth in vivo.…”
Section: Discussionmentioning
confidence: 86%